Advanced Research on Electronic Commerce, Web Application, and Communication International Conference, ECWAC 2011, Guangzhou, China, April 16-17, 2011. Proceedings, Part I - Shen, Gang.; Huang, Xiong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set CCIS 143 and CCIS 144 constitutes the refereed proceedings of the International Conference on Electronic Commerce, Web Application, and Communication, ECWAC 2011, held in Guangzhou, China, in April 2011. The 148 revised full papers presented in both volumes were carefully reviewed and selected from a large number of submissions. Providing a forum for engineers, scientists, researchers in electronic commerce, Web application, and communication fields, the conference will put special focus also on aspects such as e-business, e-learning, and e-security, intelligent information applications, database and system security, image and video signal processing, pattern recognition, information science, industrial automation, process control, user/machine systems, security, integrity, and protection, as well as mobile and multimedia communications.
Keywords: Computer science; Data protection; Information systems; Artificial intelligence; Computer vision; Computer Science; e-Commerce/e-business.; Information Systems and Communication Service; Computer Imaging, Vision, Pattern Recognition and Graphics; Systems and Data Security; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).